2004
DOI: 10.1029/2002rs002725
|View full text |Cite
|
Sign up to set email alerts
|

On the role of vertical electron density gradients in the generation of type II irregularities associated with blanketing ES (ESb) during counter equatorial electrojet events: A case study

Abstract: [1] The characteristics of different types of Sporadic E (E S ) layers and the associated plasma density irregularities over the magnetic equator have been studied in a campaign mode using VHF backscatter radar, digital ionosonde, and ground magnetometer data from Trivandrum (dip latitude 0.5°N, geographic latitude 8.5°N, geographic longitude 77°E), India. The presence of blanketing type E S (E Sb ) in the ionograms with varying intensity and duration were observed in association with afternoon Counter Equator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Whereas during solstitial months the appearance of a CEJ event and associated blanketing E s layer during the weakened EEJ condition (or CEJ) in the afternoon hours provide the necessary condition of electron density gradients in the right direction so as to generate gradient drift instabilities. Radar observations of many such events of blanketing type E s layer occurrences during the solstitial months have shown that such layer type E sb irregularities in the EEJ region give rise to strong backscattering of 54.95 MHz radar signals (Reddy and Devasia, 1977;Devasia et al, 2004). Remarkable changes in the amplitude and Doppler frequency spectra of the radar backscattered signals were observed coinciding with the appearance of blanketing E s layers in the ionograms simultaneously obtained from the colocated ionosonde at Trivandrum.…”
Section: Vhf Radar Observations Of Blanketing E S Layers and Associatmentioning
confidence: 86%
See 3 more Smart Citations
“…Whereas during solstitial months the appearance of a CEJ event and associated blanketing E s layer during the weakened EEJ condition (or CEJ) in the afternoon hours provide the necessary condition of electron density gradients in the right direction so as to generate gradient drift instabilities. Radar observations of many such events of blanketing type E s layer occurrences during the solstitial months have shown that such layer type E sb irregularities in the EEJ region give rise to strong backscattering of 54.95 MHz radar signals (Reddy and Devasia, 1977;Devasia et al, 2004). Remarkable changes in the amplitude and Doppler frequency spectra of the radar backscattered signals were observed coinciding with the appearance of blanketing E s layers in the ionograms simultaneously obtained from the colocated ionosonde at Trivandrum.…”
Section: Vhf Radar Observations Of Blanketing E S Layers and Associatmentioning
confidence: 86%
“…It may be mentioned that larger values of f b E s at the onset and growth phases of an E sb layer are indicative of the presence of very sharp electron density gradients of the E sb layer (Reddy and Devasia, 1977), which can give a large growth rate to the plasma instabilities even in the presence of a very weak electric field. The variations of f b E s with time as well as the height locations of the E sb layer in the EEJ region have important roles in the growth and sustenance of gradient instabilities during Counter Electrojet events when the east-west electric field is very weak (Devasia et al, 2004).…”
Section: E-region Electric Field Gradient In the Afternoon Hours Befomentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, blanketing Es was seen to persist over Trivandrum even during 19:45 IST (not illustrated). The occurrence of blanketing Es is also very common during the June-July period in the low-latitude ionosphere over Indian longitudes, in the solar minimum epoch (Devasia, 1976;Devasia et al, 2004). It is known that for estimating the growth rate, the field-line integrated ionospheric conductivity should be taken into account (Kelly, 1989;Sultan, 1996).…”
Section: Resultsmentioning
confidence: 99%